Study Phytoplankton as a Bioindicator of Asahan River Water Quality - Rosenta Purba, Ika (Publisher Cv. Inara, 2026)
This study aims to determine the types of phytoplankton, phytoplankton abundance, factors that influence phytoplankton life and the quality of the Asahan River based on phytoplankton abundance. The method used is descriptive. The results of the study in the waters of the Asahan River obtained 13 types of phytoplankton, with a species abundance of 4875 ind/L. The quality of the Asahan River is moderately polluted as seen from the species abundance value which ranges from 1,000-10,000 ind/L and environmental parameter values, namely temperature 28.66 ˚C, brightness 6.26 m and DO 7.19 mg/l is optimal for the growth and development of phytoplankton while the salinity of 31.22 ˚/˳, pH 6.7 and BOD 2.7mg/l are below the standard quality of the Asahan River for marine biota according to the Decree of the Minister of Environment and Forestry No. 51 of 2004.